QUALITY MANAGEMENT OF HYPERTENSION TREATMENT IN POLICLINIC OF TLOGOSARI KULON PUBLIC HEALTH CENTER - Siti Amaliah; Harits - (Universitas Muhammadiyah Semarang, 2017)
Public Health Center is a First Level Health Facility that was responsible for carrying out health development in its working area, performing Health Effort (UKM) and individual Health Effort (UKP).Quality of health services is health services in accordance with professional standards with the utilization of natural resources, efficient, effective, within the limits, the ability of the government and the community, and held safely in accordance with the code of ethics and satisfy customers with the level of satisfaction in the average population.Each Public Health Center will strive to position itself as best as possible in the eyes of customers to be trusted for fulfilling the needs in the health field.Hypertension is acondition in which systolic blood pressure ≥ 140 mmHg and / or diastolic blood pressure ≥ 90 mmHg.Hypertension is one of the major reasons of mortality and morbidity in Indonesia, and it is often referred to as a “silent killer”. Unconsciously, the sufferers experienced the complications in vital organs such as heart, brain, or kidney.The research purpose is to know the compliance level of the doctors‟ in Tlogosari Kulon Public Health Center to SOP of hypertension handling in outpatient unit and patient satisfaction. This research was a descriptive survey, the method approach used cross sectional, the sample were twodoctors at Tlogosari Kulon Public Health Center and twenty-three patients who had been suffered with hypertension in the outpatient Public Service Unit of Tlogosari Kulon Public Health Center. The priority of quality problem of hypertension handling in outpatient services used matrix problem priority method which was the lack of compliance doctors perform blood pressure checks. The reasons analysis of problems with the Paired Comparison Method were; (1) the nurse performed blood pressure checks, (2)there was only one tensimeter, (3) services in general outpatient units that did not only serve hypertensive patients, but also served all of patients, and (4) the socialization of new SOPs that had been revised was not optimal. The alternative problem solving were; (1) the procurement of two units tensimeter and made pictures of blood pressure examination, (2) using the tensimeter interchangeably and made the poster of blood pressure examination, (3)borrowing tensimeter from the other policlinics and made flipchart of blood pressure checks. The problem-solving decisions were the procurement of two units of tensimeter and made pictures of blood pressure examination.The conclusion was doctors‟ compliances with the SOP were needed to be supported by tensimeter means, therefore the quality services would increase the patient satisfaction. Keyword : Quality of Service, Hypertension, Outpatient